PROSES PENYIDIKAN TERHADAP ANAK DIBAWAH UMUR DI KEPOLISIAN RESOR KOTA SAMARINDA - Abd. Ghafur (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThis writing aims to find out how legal protection efforts are for children as perpetrators of crimes at the level of investigation, who provides legal protection for children who commit crimes.This writing aims to determine the actions of relevant agencies against minors who are in conflict with the law at the level of investigation. The type of research in this thesis is normative juridical, that is, this writing is done by reading, citing, and important notes from various primary, secondary and tertiary legal sources.Results Based on research in the field at the Samarinda City Police Agency that efforts to protect children's law as perpetrators of crimes at the level of investigation in the examination process are mediation/diversion involving the parents of the perpetrator, the victim, legal advisors, social workers, PPA (Women and Children Services). ), DKP3A (Department of Population Empowerment of Women & Children) which was formed based on the Governor's Decree 30 June 2009, P2TP2A (Integrated Service Center for Women and Children Empowerment), and BAPAS (Penitentiary). The that provides legal protection for minors suspected of committing a crime is the State through law enforcement officials, related agencies, and applicable laws.Keywords: Investigation Process, Minors.